Robotic-assisted bronchoscopy—advancing lung cancer management - Chang, Aliss T. C.; Chan, Joyce W. Y.; Siu, Ivan C. H.; Liu, Wei; Lau, Rainbow W. H.; Ng, Calvin S. H. (Frontiers in Surgery, 2025)
The incidental discovery of early-stage, multifocal lung cancer is transforming the medical landscape. Diagnosing and treating such lesions are often troublesome due to their small size, subsolid consistency, and multifocal nature. This has led to the development of electromagnetic navigation bronchoscopy, which enhanced the ease of navigation and improved localization accuracy during diagnostic procedures. Moreover, it opens the door for intricate transbronchial therapeutic procedures thanks to the superior navigational precision. To further automate navigation and increase maneuverability, robotic-assisted bronchoscopy was developed in recent years, where the robotic arms allow a high level of control and stability of the bronchoscope. Recent evidence has shown that the maneuverability, steadiness, and localization accuracy offered by robotic-assisted bronchoscopy systems with the navigation system allow operators to navigate narrower airways and perform complex interventions with great precision. This review illustrates the development, advantages, and applications of various robotic bronchoscopy systems with the latest evidence. We explore the promising future of robotic-assisted bronchoscopy, where such procedures are anticipated to play an essential role in the multidisciplinary management pathway.